Yona of the dawn. 39 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2023)
Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! The battle between Kohka and South Kai intensifies, and Hak has no choice but to disguise himself as a South Kai soldier! To make matters worse, he runs into General Rahn, with whom he has crossed swords before. Now Hak's identity as a citizen of Kohka is exposed, and he's still in enemy territory with no backup!